Determination of body weight from footprint and foot outline breadth anthropometry among Melanau ethnics of Borneo island, east Malaysia for forensic investigation - T. Nataraja Moorthy,; Hairunnisa Mohd Anas Khan, (Malaysian Society of Applied Biology, 2016)
The crime scene investigators use forensic footprint analysis to obtain vital information to solve crime. These include the estimation of stature, body weight, gender and age. Literature review shows that limited studies were conducted on body weight determination using foot impressions. This study aims to develop body weight determination models for an indigenous Melanau population residing in Borneo Island of east Malaysia from footprint and foot outline anthropometry. Footprint study results showed that breadth measurements provided better result in body weight determination than length measurements. Anthropometric measurements were made from a sample of 210 adults, with equal representation of 105 males and 105 females, following the standard procedure. Informed consent and ethical approval were obtained. The obtained data were analysed with PASW 20 computer software and developed population specific model to determine living body weight from footprint and foot outline breadth measurements. Correlation coefficient (R) values in footprint are found to be higher in the pooled sample (0.592–0.602) when compared with males (0.509–0.527) and females (0.569–0.591) separately. Correlation coefficient (R) values in foot outline are found to be higher in females (0.677-0.681) when compared with male (0.559- 0.641) and the pooled sample (0.642-0.665).